Study on Dalit Literature, Trends and Female Dalit Writings: Exploring Dalit Literature, Feminism, and Changing Trends (Journal of Advances and Scholarly Researches in Allied Education, 2019)
For society, literature is its expression. As per the definition put forth by the Oxford Advanced Learner’s Dictionary, literature is one kind of writing that is artistic, mostly the plays, poems and novels. There are several categories of literature, such as poetry, novel, short stories or drama and amongst all, the drama is the most significant when it comes to associating people’s performance. When it comes to the source of the Dalit literature, it emerges as a revolution and conflict to induce socioeconomic transformation alongside the ontology-based creation of Dalit identity in society. It elaborates different dimensions of the real concept of Dalit literature. The Dalit literature acts to deconstruct the orthodox, conservative and reactionary mentality in association with the depressed section, i.e. Dalit of the society. Feminism is no more a colossal idea. Due to dissimilarity in female's communal, political and educational circumstances, there are varied and characteristic philosophy to emphasize their domination, their marginalization and their program for freedom. Though, feminism has understood worldwide importance as a philosophy, the vitality of a variety of feminist movements is dealt in a different way in varied social enriching circumstances. This Article represents an overview on Dalit Literature, Female Dalit writers and Recent Trends.